Assing the impacts of COVID-19 on mega sporting events: A case of the 2022 FIFA World Cup in Quatar - Nasser, K.; Al-Dosari, K. A. (Global Journal of Health Sciences, 2020)
Purpose: The study sought to assess the impacts of covid-19 to the sporting industry, focusing on mega sporting events, a case of the 2022 FIFA World Cup in Qatar. The research focused on analysing the different stakeholders involved in these sporting events.